2015
DOI: 10.1371/journal.pone.0107624
|View full text |Cite
|
Sign up to set email alerts
|

When Life Got in the Way: How Danish and Norwegian Immigrant Women in Sweden Reason about Cervical Screening and Why They Postpone Attendance

Abstract: IntroductionDanish and Norwegian immigrant women in Sweden have an increased risk of cervical cancer compared to Swedish-born women. In addition, Danish and Norwegian immigrant women follow the national recommendations for attendance at cervical screening to much lesser extent than Swedish-born women. The aim of this study was to explore how Danish and Norwegian immigrant women in Sweden reason about attending cervical screening, focusing on women’s perceptions as to why they and their compatriots do not atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 39 publications
(41 reference statements)
2
54
0
Order By: Relevance
“…There is ample evidence that Asian and African women are more likely to report fear, embarrassment and shame as being responsible for delayed help-seeking regarding cancer symptoms and screening 3234. The stigma of cancer has also been reported from ethnic minorities in the UK 35,36. Although there is a need for a large quantitative study that investigates those barriers to a larger extent, our finding supports the fact that any intervention targeted toward an increased screening of Pakistani and Somali women should help address those barriers.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that Asian and African women are more likely to report fear, embarrassment and shame as being responsible for delayed help-seeking regarding cancer symptoms and screening 3234. The stigma of cancer has also been reported from ethnic minorities in the UK 35,36. Although there is a need for a large quantitative study that investigates those barriers to a larger extent, our finding supports the fact that any intervention targeted toward an increased screening of Pakistani and Somali women should help address those barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The immigration status of women has been mentioned in studies such as those of Azerkan et al (2015) and Jackowska et al (2012) to be one of the reasons for the perceived barrier of migrant women to undertaking screening in host countries.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Azerkan et al (2015) among Danish and Norwegian immigrant women in Sweden found out that women do not actually understand the essence of the Pap smear test if there were no precancerous symptoms. The essence of the Pap test is to detect and diagnose precancerous signs in the woman's cervix before it results in advanced cancer (Leyden et al, 2005).…”
Section: Cervical Cancer As a Global Issuementioning
confidence: 99%
“…Some immigrants may choose not to selfsample because they prefer seeking health care in their country of origin (50,51). Finally, the migration process itself may be a stressor limiting the time and mental resources to participate in preventive care (52).…”
Section: Potential Reasons For Nonparticipation In Self-samplingmentioning
confidence: 99%